Gender Representation in Moroccan Orature: Moroccan Folktales as a Case Study - ElFalih, Tarik; El Idrissi, Zakariae (International Journal of Language and Literary Studies, 2024)
Scholars worldwide are fascinated by oral traditions, and Moroccan folktales are particularly striking within a mosaic of spoken narratives and cultural past. Storytellers bring these stories, rich in traditional wisdom, to life in both public and private spaces. To showcase their storytelling abilities, women are assuming roles that have historically been held by men, such as "storyteller" and "orator." Researchers are now examining the forms in which women are portrayed in these tales, as well as how female narrators engage with and contest these representations within the oral tradition. This paper looks at the stories that women tell and how often they connect female characters to negative stereotypes like evil intent, jealousy, and deceit through an exemplifying analytical approach. While these tales demonstrate women's storytelling abilities, they also reveal women's self-doubt and uncover women’s underestimation of themselves and their intellectual abilities, hence showing the contradictions residing in female-narrated stories. Thus, one should advocate for a revised view of the female voice in storytelling.